Computational Fluid Dynamics Of Urinary Catheterization - Nazry, Farah Aisyah (Universiti Sains Malaysia, 2018)
Urethral catheterization is a medical procedure that helps the drainage of urinary bladder for patients that have difficulties urinating naturally. An urinary catheter is a flexible tube that collects urine from human bladders, straight to the drainage bag. There are many complications faced by the patients such as urinary tract infections (UTIs) ,bladder spasms, leakage, blood in catheter tube and bladder stones. Thus, this project will determine the best diameter and configuration of the catheter to optimize the mass flow rate using Computational Fluid Dynamic (CFD) in ANSYS Fluent software. To mimic the characteristics of urine, instead of using water as fluid (water has the closest characteristic as urine).The objectives of this simulation are tto investigate the effect of diameters and configuration of urinary catheter tube in urinary catheterization system using Computational Fluid Dynamics (CFD) technique and to optimize the diameter and configuration of the urinary catheter tube. From five different configurations, an L-shaped configuration showed the best mass flow rate and pressure gradient. This parameters will help in preventing any encrustration happening on the wall of catheter. Subsequently, from this configuration, five different cases that represented five different diameters were then simulated to find the most releven diameter for human usage. From all the simulations a catheter with diameter CH18 in an L-shaped configuration showed the best result possible. In conclusion, understanding the parameters for a safe and healthy usage of urinary catheter are important for future application.